HUBUNGAN ANTARA PENGGUNAAN INSTAGRAM DENGAN EFEKTIVITAS DAKWAH PADA AKUN @SHIFTMEDIA.ID - Hasanah, Nadya Ushwah; Abdurrazaq, Muhammad N (Journal of Islamic Studies, 2023)
Instagram as the platform which provides sophisticated features is utilized by da’wah account to make da’wah content. This undergraduate thesis studied the correlation between the usage of Instagram and da’wah effectiveness in account @shiftmedia.id (case study: the feed entitled “Self Improvement”). The first main problem in this research was the existence of correlation between Instagram usage and da’wah effectiveness in account @shiftmedia.id (case study: the feed entitled “self improvement). The second main problem was how big was the influence between the usage of Instagram and da’wah effectiveness in The research result showed that there was significant evidence. Based on pearson correlation test which had been conducted in general there was sufficient correlation value with the result as follows: cognitive effect dimension and definition dimension showed sufficient correlation result with pearson correlation value in each indicator that had been tested namely 0,397 and 0,259, behavioral effect dimension and action dimension showed sufficient correlation result with pearson correlation value in each tested indicator namely 0,409; 0,447; 0,446 dan 0,578, affective effect dimension and attitude influencing dimension showed sufficient correlation result and strongly weak with pearson correlation value in each tested indicator namely 0,369 and 0,154.